ROLE OF NON-GOVERNMENTAL HUMANITARIAN ORGANIZATIONS IN TIME OF INTERNAL ARMED CONFLICT CASE STUDY AFGHANISTAN (Proceedings of the International Conference on Social Sciences, 2018)
Non-governmental humanitarian organizations provide humanitarian assistance to armed conflicts and disasters. Different type of non-governmental humanitarian organizations operates in locally and internationally such as local non-governmental humanitarian organizations and international non-governmental humanitarian organizations. These organizations are responsible in providing humanitarian aid according to the humanitarian principles. This research mainly focus on neutrality principle of non-governmental humanitarian organizations in times of internal armed conflict of Afghanistan.The objectives of the research are to identify vital role of non-governmental humanitarian organizations in internal armed conflict of Afghanistan and effectiveness of NGOs. Methodologyconsist of secondary data obtained from secondary sources , published materials such as newspapers, reports , books journal articles and  annual reports etc Qualitative data taken from  opinions, ideas, stories and case histories .These can be obtained from both primary and secondary data. This research mainly based on qualitative study.It can be concluded that non-governmental organizations vital role based on neutrality principle in Afghanistan internal armed conflict . But there arguments that the neutrality principle can be changed according to complex humanitarian strategies of current global order.
Keywords: Non-Governmental Humanitarian Organizations; Internal Armed Conflict; Neutrality